Electrocardiographic Features of Arrhythmogenic Right Ventricular Dysplasia/Cardiomyopathy According to Disease Severity: A Need to Broaden Diagnostic Criteria - Nasir, Khurram; Bomma, Chandra; Tandri, Harikrishna; Roguin, Ariel; Dalal, Darshan; Prakasa, Kalpana; Tichnell, Crystal; James, Cynthia; Jspevak, Phillip; Marcus, Frank; Calkins, Hugh (Circulation (New York, N.Y.), 2004)
Background— The purpose of this study was to systematically study diagnostic and prognostic electrocardiographic (ECG) characteristics of arrhythmogenic right ventricle dysplasia/cardiomyopathy (ARVD/C). Methods and Results— The patient population included 50 patients with ARVD/C (27 males, 23 females; mean age 38±15 years). We also analyzed the ECG of 50 age- and gender-matched normal control subject and 28 consecutive patients who presented with right ventricular outflow tract (RVOT) tachycardia. Right bundle-branch block (RBBB) was present in 11 patients (22%). T-wave inversions in V 1 through V 3 were observed in 85% of ARVD/C patients in the absence of RBBB compared with none in RVOT and normal controls, respectively ( P <0.0001); epsilon waves were seen in 33%, and a QRS duration ≥110 ms in V 1 through V 3 was present in 64% of patients. Among those without RBBB, our newly proposed criterion of “prolonged S-wave upstroke in V 1 through V 3” ≥55 ms was the most prevalent ECG feature (95%) and correlated with disease severity and induction of VT on electrophysiological study. This feature also best distinguished ARVD/C (diffuse and localized) from RVOT. Conclusions— A prolonged S-wave upstroke in V 1 through V 3 is the most frequent ECG finding in ARVD/C and should be considered as a diagnostic ECG marker.